2016
DOI: 10.3390/nu8070443
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes-Specific Nutritional Formulas versus Oatmeal on Postprandial Glucose, Insulin, GLP-1 and Postprandial Lipidemia

Abstract: Diabetes-specific nutritional formulas (DSNFs) are frequently used as part of medical nutrition therapy for patients with diabetes. This study aims to evaluate postprandial (PP) effects of 2 DSNFs; Glucerna (GL) and Ultra Glucose Control (UGC) versus oatmeal (OM) on glucose, insulin, glucagon-like peptide-1 (GLP-1), free fatty acids (FFA) and triglycerides (TG). After an overnight fast, 22 overweight/obese patients with type 2 diabetes were given 200 kcal of each of the three meals on three separate days in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 34 publications
(44 reference statements)
8
32
0
2
Order By: Relevance
“…Several explanations could be presumed. Participants in structured NT groups consumed more protein and fiber, which are known to improve postprandial blood glucose levels [ 21 24 ]. Use of structured menus and snacks provided consistent ratio of macronutrients and energy intake per meals that might reduce blood glucose variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several explanations could be presumed. Participants in structured NT groups consumed more protein and fiber, which are known to improve postprandial blood glucose levels [ 21 24 ]. Use of structured menus and snacks provided consistent ratio of macronutrients and energy intake per meals that might reduce blood glucose variability.…”
Section: Discussionmentioning
confidence: 99%
“…Use of structured menus and snacks provided consistent ratio of macronutrients and energy intake per meals that might reduce blood glucose variability. Use of DSNFs, within the total daily energy intake, had its own benefit on glycemic control, [ 25 ] insulin and GLP-1 secretion, [ 21 ] and body weight [ 26 , 27 ]. Taken together, these factors might explain the improvement in glycemic control, body weight, body composition and insulin sensitivity in response to structured NT.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized diabetes-specific formulas (DSF) are designed using low glycemic index and slowly digested carbohydrates and monosaturated fatty acids to support glycemic control [81][82][83]. Systematic reviews and meta-analyses have shown that DSF as part of lifestyle interventions effectively improves glycemic control and reduces cardiometabolic risks [84,85].…”
Section: Evidence For the Use Of Complete And Balanced Nutritional Sumentioning
confidence: 99%
“…Several meal replacement formulas have been tested for weight management [ 47 ]. We previously showed that patients with T2D who consumed DSF for breakfast had a lower glucose excursion compared to oatmeal with the same calorie content [ 48 ]. Several DSFs were used in both the Look AHEAD study and the Why WAIT program for the initial 6–20 weeks to enhance initial weight reduction [ 39 ].…”
Section: Components Of Multidisciplinary Approachmentioning
confidence: 99%